2018
DOI: 10.3892/mmr.2018.8617
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of the NF‑κB signaling pathway in colon cancer cells by the natural compound Riccardin D from Dumortierahirsute

Abstract: Colorectal cancer (CRC) is a major cause of mortality and morbidity. Chronic inflammation is closely associated with the development, progression and prognosis of the majority of intestinal malignancies. In recent years, targeting the nuclear factor (NF)-κB signaling pathway for CRC therapy has become an attractive strategy. Riccardin D, a novel macrocyclicbis (bibenzyl) compound, was isolated from the Chinese liverwort plant. Previous studies have suggested that Riccardin D exerted chemo-preventative effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 36 publications
2
16
0
Order By: Relevance
“…NF-κB's enhanced expression may be attributed to chronic in ammation followed by cyclic administration with carcinogen, DMH contribute to colon carcinogenesis. Other studies also decipher that colon cancer cell lines have remarkably abnormal NF-κB expression and less IκB levels, unravelling that dysregulated NF-κB is a major contributor of colon cancer which is in accordance to our results as well [41]. Our results further validate that the piperine inhibits NF-κB activity as reported previously and strongly recommend that the bioactivity of piperine against colon carcinogenesis may possibly be due to inactivation NF-κB which is further evident due to inhibition of downstream pathway player proteins [7,42,43].…”
Section: Discussionsupporting
confidence: 92%
“…NF-κB's enhanced expression may be attributed to chronic in ammation followed by cyclic administration with carcinogen, DMH contribute to colon carcinogenesis. Other studies also decipher that colon cancer cell lines have remarkably abnormal NF-κB expression and less IκB levels, unravelling that dysregulated NF-κB is a major contributor of colon cancer which is in accordance to our results as well [41]. Our results further validate that the piperine inhibits NF-κB activity as reported previously and strongly recommend that the bioactivity of piperine against colon carcinogenesis may possibly be due to inactivation NF-κB which is further evident due to inhibition of downstream pathway player proteins [7,42,43].…”
Section: Discussionsupporting
confidence: 92%
“…Hiroshi et al processed gene expression microarray and Western blot analysis, and found that E2F pathway was down‐regulated in colon cancer cells. Besides, targeting NF‐κB signalling pathway for CRC therapy has confirmed to be an effective strategy for colon cancer treatment . In addition, miR‐377 was also confirmed to target specificity protein 1, and further inhibit invasion and proliferation of glioblastoma cells .…”
Section: Discussionmentioning
confidence: 92%
“…[ 39,40 ] Previous studies have revealed a similar pattern of inhibition of breast cancer cells in Riccardin D induced apoptosis. [ 41 ] Altogether, these results suggested that following NF‐κB inhibition, crocin may induce apoptosis via modulating the MAPK‐regulated apoptotic signaling pathway. Hence the crocin can be a potential alternative agent to treat the thyroid cancer in future.…”
Section: Discussionmentioning
confidence: 96%